Utilisation of supplementary prenatal screening and diagnostics in Germany: cross-sectional study using data from the KUNO Kids Health Study - Johanna Mayer; Susanne Brandstetter; Christina Tischer; Birgit Seelbach-Göbel; Sara Fill Malfertheiner; Michael Melter; Michael Kabesch; Christian Apfelbacher; KUNO Kids Study group (BMC, 2022)
Abstract Background Appropriate health system utilisation during pregnancy is fundamental for maintaining maternal and child's health. To study the use and determinants of supplementary prenatal screening and diagnostics in Germany this study provides comprehensive data. Methods We obtained data from a recently established prospective German birth cohort study, the KUNO Kids Health Study. Analyses are based on Andersen's Behavioural Model of health system use, which distinguishes between predisposing (e.g. country of birth), enabling (e.g. health insurance) and need factors (e.g. at-risk pregnancy). We examined bi- and multivariate association with the use of supplementary prenatal screening and diagnostics using logistic regression. Results The study has a sample size of 1886 participating mothers. One fifth of the mothers investigated did not use any supplementary prenatal screening or diagnostics. Notably, the chance of using supplementary prenatal screening and diagnostics more than doubled if the pregnant woman had a private health insurance (OR 2.336; 95% CI 1.527-3.573). Higher maternal age (OR 1.038; 95% CI 1.006-1.071) and environmental tobacco smoke exposure (OR 1.465 95% CI 1.071-2.004) increased the use of supplementary prenatal screening and diagnostics. However, regarding need factors only having an at-risk-pregnancy (OR 1.688; 95% CI 1.271-2.241) showed an independent association. Conclusion The important role of the type of health insurance and the relatively small influence of need factors was surprising. Especially with respect to equity in accessing health care, this needs further attention.